Effectiveness of Computed Tomography Density Value in the Differential Diagnosis of Benign and Malignant Renal Lesions - Sercan ÖZKAÇMAZ; İlyas DÜNDAR; Nazım KANKILIÇ; Mesut ÖZGÖKÇE; Abdullah GÜL; Rahmi ASLAN (Ahi Evran Medical Journal, 2021)
Purpose: We aimed to investigate the role of mean Hounsfield Unit(HU) values measured on enhanced or unenhanced Computed Tomography(CT) images for the differentiation of benign and malignant kidney lesions.